Metamorphic studies in the Scottish Highlands - Baker, A; Baker, Andrew James (1985)
﻿ Conditions of 8kb and 800°C are estimated for sillimanite K feldspar bearing metapelites and garnet-clinopyroxene bearing amnphibolites in Glen Muick. These conditions are inconsistent with the simultaneous nearby presence of equilibrium between andalusite and kyanite. Andalusite in the Glen Muick area is late. The sillimanite zone may have been in part primary. There is a transition without major structural break between Tay Nappe flat belt and the "Banff Nappe". A dataset has been derived for phases in the system KCMASHCO2. The MHSRK equation of Kerrick and Jacobs (1981) has been used to extract data from mixed devolatilisation equilibria. Heats of formation are in agreement with calorimetrically determined values. Phlogopite equilibria calculated using disordered phlogopite data seem most appropriate to natural metapelite assemblages. Variations in pressure and temperature have been constrained across the Dalradian using various calibrated reactions. Temperatures vary from about 500°C in the low kyanite zone to 800°C in the sillimanite-K feldspar zone and pressures vary from 4kb to 10kb. Pressure estimates are justified on the basis that they are consistent with the aluminosilicate phase diagram. Rocks from the Central Highlands to Glen Clova underwent a decrease in pressure during evolution through peak metamorphic conditions. Amphibolites from the southern Moines show evidence of a former eclogitic assemblage of early Grampian age or earlier. High temperature regional metamorphic rocks lie at high structural levels and are are suggested to be an allochthonous unit, the Banff Nappe of Grampian age. The western margin of the Banff Nappe is marked by a temperature maximum to the immediate east, sharp thermal transitions, a train of metabasites and a high strain zone. It is suggested that emplacement of a Banff Nappe resulted in the deformation and metamorphism of structurally lower rocks.